INDIAN POTATO PROCESSING STORY: INDUSTRIAL LIMITATIONS, CHALLENGES AHEAD AND VISION FOR THE FUTURE - Pandey, S. K.; Marwaha, R. S.; Kumar, Dinesh; Singh, S. V. (Potato Journal, 2013)
Potato processing scenario in India has completely changed in the last ten years after the release of India’s first processing varieties, Kufri Chipsona-1 and Kufri Chipsona-2, in 1998 by the Central Potato Research Institute, Shimla followed by Kufri Chipsona-3 in 2005 and Kufri Himsona in 2007. About 30 Indian and multinational companies manufacturing potato chips, flakes and French fries have been installed in all the four zones of India from just 4 or 5 companies in 2003. Currently about 4% of total potato produce is being processed in organized and unorganized sector. The unavailability of good quality processing potatoes in desired quantities throughout the year is the main bottleneck for the processing industries. Other major requirements include development of suitable varieties for French fries; early maturing processing varieties for plateau region; development of temperature insensitive processing varieties; breeding varieties resistant to cold sweetening; specific breeding for problematic regions; development of yield and quality enhancing technologies for processing varieties; finding low-cost alternative storage technology; improving infra-structural facilities and developing inexpensive technologies for the production of diverse potato products. A comprehensive, viable and economical scheme for supplying processing potatoes to the industries round the year has been devised which will help the industries in planning the supply from the nearest locations. The new arising challenges have been highlighted and concrete remedial measures have been suggested.